Trichuris trichiura infection and cognition in children: Results of a randomized clinical trial - Wong, Michael S.; Grantham-McGregor, Sally M.; Simeon, Donald T. (My University, 1995)
The effects of mild to moderate infections of Trichuris trichiura on cognitive functions were investigated in Jamaican children aged 7-10 years. In all 189 infected children and 100 uninfected classmates we studied. The infected children were randomly assigned to receive treatment (albendazole) or a placebo. All children were given cognitive tests at the time of enrolment and 14 weeks later. These included verbal fluency (generation of ideas), digit span (working memory), number choice (speed of processing of visual stimuli), visual search (sustained attention), and French vocabulary test (paired-associate learning). At baseline, the infected children had lower scores than the uninfected in fluency, search, and French. Treatment effects were examined among infected children and there was no significant treatment by weight-for-age interaction in fluency. The children with low weight-for-age improved with treatment while there was no improvement with treatment among the older children. It was concluded that treatment of children with mild to moderate T. trichiura infections using albendazole produces little benefit on cognition if they are adequately nourished; however, under-nourished children are more likely to benefit.
doi: 10.1017/S0031182000064799
Keywords: Cognitive processes